Keunggulan Dari E-Bisnis Di Pasar Global - Teddy Hikmat Fauzi (SOSIALITA, 2011)
As the effect of phenomenal technology there is a significant correlation between communication technology and information technology which supports the spread of information web locally, regionally and globally such as internet world wide web, electronic mail, electronic shopping, electronic education, electronic meeting and electronic banking which are all the parts of electronic business activities known as electronic business. In fact , electronic business is the main business process such as in internet use and digital technology as the direct communication which are arranged transformatively and are able to provide values and advantages for the business world.